INVESTIGAÇÕES CULTURAIS E GEOARQUEOLÓGICAS DA ETNIA KONDURI A PARTIR DE REGISTROS CERÂMICOS - LOPES, Camila da Costa (Universidade Federal do Oeste do Pará, 2022)
This dissertation presents the result of cultural, georheological and anthropological investigations of the extinct Konduri ethnic group, during the period of contact between Europeans and local peoples from the Lower Amazon region during the colonization period. Reports pointed out that they lived in the 5th to the 17th centuries, in the region where the cities of Nhamundá, Oriximiná, Faro and Óbidos are located. The objectives of our research are to investigate the cultural and identity formation of the Konduris from geoarchaeological records and analyses of ceramic pieces of the Lower Amazon region. The research was divided in three moments. The first concerns the state of the art, about reports of chroniclers who sailed the Amazon River in the researched region, between the 16th and 17th centuries, such as Orellana and Acunã. In the second moment, quantitative and qualitative analyses were performed, describing 20 ceramic fragments under the safeguard of the Integrated Museum of Óbidos (MIOB), found in the community of Arapucu, in accordance to recognized Konduri-style references, as well as statistical balance on Konduri-style characteristics. In the third moment, the geo-archaeological-archaeometric analysis was done through X-ray diffraction techniques - XRD, to identify mineralogical phases of ceramic component materials, and Scanning Electron Microscopy (SEM), to characterize clay and the resistance conditions of ceramics. The results allowed us to state that the investigated pieces are characteristic of the Konduri style, and show rectilinear, curvilinear and random incisions, application and punctuation of the pieces, as well as the presence of zoomorphic and anthropomorphic appendages, as well as ‘cauxi’ presence. This confirms archaeological references of the region and makes possible to suggest that the indigenous group was concern in improving the mechanical resistance of the ceramic pieces.